1997
DOI: 10.1016/s0008-6363(97)00181-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive pressure on both femoral venous and arterial blood velocities and the cutaneous microcirculation of the forefoot

Abstract: Positive pressure on the full leg provided no significant beneficial effect on femoral venous blood velocity. Whereas we showed that for an external uniform pressure as low as 10 mmHg, significant impairments in both arterial inflow of the lower limb and microcirculation of the forefoot appeared in recumbent healthy young subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the upper portion of the leg, the common femoral vein (CFV) of acute DVT patients can vary from 5.00–21.70 mm in diameter, while the popliteal vein varies from 3.80–14.40 mm (Hertzberg et al, 1997). Blood flow velocities in the CFV varies widely from 6 cm/s to 40 cm/s, as found from a study of young healthy adults (Fromy et al, 1997). In DVT patients, the blood flow downstream from the occluded or partially occluded vein where the treatment is needed would be slower.…”
Section: Discussionmentioning
confidence: 68%
“…In the upper portion of the leg, the common femoral vein (CFV) of acute DVT patients can vary from 5.00–21.70 mm in diameter, while the popliteal vein varies from 3.80–14.40 mm (Hertzberg et al, 1997). Blood flow velocities in the CFV varies widely from 6 cm/s to 40 cm/s, as found from a study of young healthy adults (Fromy et al, 1997). In DVT patients, the blood flow downstream from the occluded or partially occluded vein where the treatment is needed would be slower.…”
Section: Discussionmentioning
confidence: 68%
“…From a theoretical point of view, there is, despite all positive effects on the venous macro-circulation, the possibility of a compression-related negative net balance of the capillary perfusion. Results from Fromy et al 26 support this hypothesis. In their own material, the tcpO 2 decreased by 5-10% over the treatment period when using regular compression stockings; whether or not this difference is of clinical relevance remains unknown, although, overall positive effects of compression seem to outweigh negative ones as shown by clinical outcome studies.…”
Section: Discussionmentioning
confidence: 87%
“…72,73 Oedema and/or venous ulcers in mixed pathology CVI or lymphoedema and/or PAOD Compression does not always reduce arterial inflow, as several experiments have demonstrated that the use of compression can even lead to an increased arterial flow in healthy individuals. [74][75][76] Because arterial occlusive disease is a frequent condition, especially in older age groups, this applies particularly to patients with venous and lymphatic diseases. In a population of 1416 patients with VLUs, 16% had concomitant arterial occlusive disease, 2% had critical ischaemia and 14% had an ABPI between 0.5 and 0.85.…”
Section: Oedema In Heart Failurementioning
confidence: 99%